Tribology : a simple guide to the study of friction - Watterson, James M. (Engineering technology collection., 2019)
Tribology is the scientific and engineering study of friction, and in common practice; it most often involves the control and reduction of friction. This is particularly critical to the successful and continued operation of moving parts. This book addresses the types of seals and bearings that are commonly found in most rotating and moving machinery, including how they are designed, how they work and what can be done to ensure that they continue maintain proper lubrication and successful operation. The author discusses the critical lubrication issues dealt with in gears and gear boxes, focusing on specific types of mechanical seals, including compression seals, hydrodynamic seals, hydrostatic seals, and mechanical face seals. Dr. Watterson also introduces the reader to the major types of bearings, including roller bearings, ball bearings and various types of sealed bearing systems, and their maintenance and lubrication requirements.